Innovative CSR : from risk management to value creation - Louche, Céline; Idowu, Samuel O.; Leal Filho, Walter (Greenleaf Publishing, 2010)
By and large, corporations of the 21st century have come to realize that their obligations to societies in terms of corporate social responsibility are fourfold: economic, ethical, altruistic and strategic. This book aims to explore, inspire and support creative, innovative and strategic corporate social responsibility (CSR).